POWERING CUSTOMER CONNECTIVITY OF PRODUCTS WITH LAST MILE SUPPORT SERVICES: EVIDENCES FROM INDIAN PASSENGER CAR MANUFACTURING - Jasial, Sumeet Singh; Pal, S S; Bansal, Sanjeev (Brazilian Journal of Operations & Production Management, 2017)
The paper highlights post-production customer connectivity processes in an automobile manufacturing set-up. Identity of post-production processes has been established as a unique in company service operations or pseudo-manufacturing activities. Consequently this research observes that handling these activities purely with a manufacturing focus or with a pure service focus would not be that effective. This paper in-turn proposes a new approach to powering the customer connectivity process in the last mile of a product’s journey from manufacturing to market. The scenario has been addressed in three domains, viz., Post-Production pre-market functions, Product Installation, and Product Liabilities. Through a composite process map of the post-production situations it captures the order winning elements to pick up opportunities for the possible reinforcement of adding value for money in the last mile activities on the product from company to customer.